Rekognisi Pembelajaran Online di Program Studi Pendidikan Teknologi Informasi FKIP Universitas Lampung - Sagala, Margaretha Karolina; Pramudiyanti, Pramudiyanti; Rinaldi, Daniel (Universitas Lampung, 2024)
Education is a means of forming a generation that is intelligent and has character. This means that education plays an important role in creating and improving the quality of human resources. However, in reality, the FKIP Information Technology Education Study Program does not have adequate facilities, especially in terms of classrooms. This results in lecturers and students having to optimize online learning by using Unila's platforms, namely VClass, Zoom, and g-meet, including WhatsApp Group. This study aims to: (1) Analyze the recognition of online learning in the Information Technology Education Study Program; (2) Analyze the type of online learning applied in the Information Technology Education Study Program; and (3) Analyze the factors that cause lecturers and students to not optimally use online learning. The design of this study is qualitative descriptive. The population in the study is students of the Information Technology Education Study Program (PTI) FKIP University of Lampung. The sample in this study is PTI students who take online courses for the 2023-2024 Academic Year. Answering the research question, qualitative data was analyzed using descriptive statistics. The data from the questionnaire is presented as frequency and percentage. Data from the interview are described. The findings obtained from the questionnaire were then analyzed with interview data. Based on the results of the research, it is concluded that: (1) The recognition of online learning in the Information Technology Education Study Program has not been implemented optimally; (2) The type of online learning applied in the Information Technology Education Study Program is not optimal because there is no overall awareness of lecturers and students to carry out online learning; (3) The factors that cause lecturers and students to not optimally use online learning are that lecturers have not prepared learning tools as a whole and students are less independent in carrying out online learning.Kata kunci: Pembelajaran Online, Pendidikan Teknologi Informasi, Rekognisi